Pengaruh People dan Physical Facilities terhadap Kepuasan Konsumen di Mixue Ciparay - Shifa Nurfitria HR; Triyani Triyani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid growth of franchise-based beverage outlets in Indonesia has intensified competition, making service quality and physical environment critical determinants of customer satisfaction. This study addresses existing service and facility-related issues observed at the Mixue Ciparay outlet, which may affect customer perceptions and repeat visits. The purpose of this research is to examine the influence of people and physical facilities on customer satisfaction at Mixue Ciparay. A quantitative approach was employed using a survey method. Data were collected from 100 customers through structured questionnaires and analyzed using SPSS version 27. The analysis included validity and reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that people have a positive and significant effect on customer satisfaction (t = 2.830; p < 0.05), while physical facilities show a stronger positive and significant influence (t = 5.770; p < 0.05). Simultaneously, both variables significantly affect customer satisfaction (F = 77.738; p < 0.05), explaining 61.6% of the variance. These findings highlight that customer satisfaction in franchise beverage outlets is shaped by the combined role of employee service quality and well-managed physical facilities, emphasizing the need for balanced operational management at the outlet level.